South African cultural adaptation and Northern Sotho translation of the modified checklist for autism in toddlers, Revised, with follow-up - Kritzinger, Alta M. (Aletta Margaretha) (University of Pretoria, 2022)
Thesis (PhD (Speech-Language Pathology))--University of Pretoria, 2021.